2015
DOI: 10.1016/j.nicl.2015.07.013
|View full text |Cite
|
Sign up to set email alerts
|

Increased contrast enhancing lesion activity in relapsing–remitting multiple sclerosis migraine patients

Abstract: Background and objectivesWhile the literature supports the idea that multiple sclerosis (MS) and migraine are related, the exact mechanism(s) of this association is not well understood. Observations of increased contrast enhancing (CE) lesion activity in individual MS patients suffering from migraine prompted us to determine a relationship between migraine and MRI outcomes in a large cohort of MS patients.MethodsWe included 509 MS and 64 clinically isolated syndrome (CIS) patients and 251 age- and sex-matched … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
16
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 41 publications
1
16
0
Order By: Relevance
“…Previous studies have suggested that migraines were linked to CIRDs [22,23]. We hypothesized that such a link might be explained by systemic inflammation, which might potentiate the neurogenic inflammation associated with migraines, as suggested in multiple sclerosis [10,24,25]. In the present study, systemic inflammation was never associated with migraine.…”
Section: Discussionsupporting
confidence: 46%
“…Previous studies have suggested that migraines were linked to CIRDs [22,23]. We hypothesized that such a link might be explained by systemic inflammation, which might potentiate the neurogenic inflammation associated with migraines, as suggested in multiple sclerosis [10,24,25]. In the present study, systemic inflammation was never associated with migraine.…”
Section: Discussionsupporting
confidence: 46%
“…It has been considered the MRI hallmark for monitoring of MS. The inflammatory component of the disease is usually present in earlier stages of MS lesions [10] .…”
Section: Discussionmentioning
confidence: 99%
“…MS patients may experience both pain and spasticity, and pain secondary to spasticity or painful tonic spasms is a subtype of nociceptive pain frequently reported in MS (Solaro et al, 2018). Among primary headaches, migraine was reported to be three times more frequent in MS patients than in the general population, to carry a considerable disability, and to be associated with a more symptomatic course and an increased contrast enhancing lesion activity compared to MS patients without headache (Kister et al, 2010;Graziano et al, 2015).…”
Section: Introductionmentioning
confidence: 99%